Interpreting precedents : a comparative study - MacCormick, Neil; Summers, Robert S. (Applied legal philosophy, 1997)
This work seeks to advance understanding of the fundamentals of law and its methodology through systematic comparative and theoretical analysis. The research group seeks to achieve this by using an agreed set of concepts and terminology in the analysis of common topics.